Dynamic, Playful and Productive Literacies. Issue 2 (3rd April 2018) - Cannon, Michelle; Potter, John; Burn, Andrew
Abstract: This paper reflects on recent projects in a variety of media forms, in both formal and informal educational settings, discussing ways of expanding our notions of literacy practices which reflect their place in the wider lived experience of digital culture. We have collected these reflections under three headings. The first of these, Dynamic Literacies, presents an overarching view of literacy as both ideological, following the 'new literacy studies', and dynamic, incorporating both semiotic and sociocultural versions of literacy in ways which reflect the changing nature of lived experience in the digital age. The second strand, Productive Literacies, constructs an argument around digital making practices with younger learners which views these as media crafting, critique and artistry. The third strand, Playful Literacies, explores recent projects which are located in games and game-authoring practices as a specific example of connecting pedagogy to contemporary media forms and learner agency in formal and informal settings. Taken together, the three perspectives allow for common ground to be established between multimodal production practices, whilst providing suggestions for framing literacy pedagogy in response to the pervasive use of media and technology in contemporary digital culture.